Ordinary Jerusalem, 1840-1940 : opening new archives, revisiting a global city - D̲alachanēs, Angelos; Lemire, Vincent, 1973- (Open Jerusalem (Series), 2018)
In Ordinary Jerusalem, 1840-1940, Angelos Dalachanis, Vincent Lemire and thirty-five scholars, mostly young academics, utilize new archives to revisit the global, extraordinary city of Jerusalem in the late Ottoman and Mandate periods.